The Rise of Financial Technology and Its Credit Risk in Indonesia - Grisvia Agustin (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2023)
The purpose of the study is to use VECM to examine credit risk, basic loan interest rate, the number of lending entities, and the total amount of outstanding loans for fintech companies. Fintech is expanding quickly in Indonesia, even during the Covid 19 pandemic. In March 2019 until the present, Indonesia has formally entered the Covid 19 epidemic, causing Indonesia’s GDP growth in 2020 to be -2.07. However, Indonesia’s outstanding fintech loans are still sharply rising. Fintech businesses offer numerous financial services and can connect with the unbanked. Because a fintech firm tries to offer ease, particularly for customers who have trouble accessing traditional banks, credit through a fintech company is an easy loan to approve. Profit and credit risk are increased for fintech enterprises. As a result, interest rates have a short-term influence on outstanding loans because Fintech lending companies derive revenue from activities and services based on fees and interest. Fintech financing has extremely minimal credit risk, is below OJK’s criteria, and has no immediate or long-term effects on outstanding loans. The number of lender entities significantly impacts outstanding long-term loans to fintech companies.